Prenatal ultrasonographic diagnosis of generalized arterial calcification of infancy. Issue 1 (13th January 2014) - Corbacioglu Esmer, Aytul; Kalelioglu, Ibrahim; Omeroglu, Rukiye Eker; Kayserili, Hulya; Gulluoglu, Mine; Has, Recep; Yuksel, Atıl
ABSTRACT A healthy 19‐year‐old nulliparous pregnant woman was referred to our clinic because of fetal pericardial effusion and ascites. The sonographic examination performed at 28 weeks' gestation revealed scalp edema, severe skin edema, bilateral hydrocele, ascites, and pleural and pericardial effusion. Fetal echocardiographic examination showed that both ventricles were dilated with severely depressed contractility. The aortic annulus, ascending aorta, aortic arch, descending aorta, common iliac arteries, main pulmonary artery, tricuspid valve, and mitral chordae tendinae were hyperechogenic. Right ventricular outflow tract was narrow with decreased blood flow. There was tricuspid and mitral valve regurgitation and tricuspid valve stenosis. On the basis of these findings, we made the diagnosis of generalized arterial calcification, which is characterized by extensive calcification of internal elastic lamina and intimal proliferation of medium‐sized and large arteries. This diagnosis was confirmed histologically after the termination of pregnancy. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:50–54, 2015